Method for producing optical laminate and intermediate laminate used in the method

By using a stacked structure of a polarizer, an adhesive layer and a phase difference layer in the manufacturing of the optical laminated body, and stably peeling with a peeling auxiliary member, the problem of poor peeling of the liquid crystal film is solved, and a high-quality appearance of the optical laminated body is achieved.

CN119738906APending Publication Date: 2025-04-01NITTO DENKO CORP
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411226053.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-03
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When manufacturing liquid crystal films, peeling the oriented substrate may lead to poor peeling, affecting the appearance quality of the optical laminate.

Method used

The optical laminate manufacturing method is adopted that includes a polarizer, an adhesive layer and a phase difference layer in sequence. The polarizer, a phase difference layer and a support substrate are laminated by the adhesive layer, and the stripping auxiliary member is used to contact the side surface of the polarizer of the intermediate laminate to achieve stable peeling of the optical laminate.

Benefits of technology

It effectively suppresses poor appearance such as wrinkles and damage, and obtains an optical laminate with extremely excellent appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119738906A_ABST
    Figure CN119738906A_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing an optical laminate having excellent appearance and an intermediate laminate used in the manufacturing method. The manufacturing method of an optical laminate according to an embodiment of the present invention is a method for manufacturing an optical laminate comprising a polarizer, an adhesive layer, and a phase difference layer in sequence, the manufacturing method comprising: a step of laminating a laminate of the polarizer, the phase difference layer, and a supporting substrate with the aid of the adhesive layer to produce an intermediate laminate; and a step of bringing a peeling auxiliary member into contact with a surface of the intermediate laminate on the polarizer side to peel the optical laminate from the supporting substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an optical laminate and an intermediate laminate used in the production method. Background Art

[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (such as organic EL display devices, inorganic EL display devices) have rapidly become popular. In image display devices, optical laminates containing phase difference films are used in most cases. In recent years, as the demand for thinning of image display devices has increased, the demand for thinning of optical laminates has also increased. For the purpose of thinning of optical laminates, the thinning of phase difference layers (phase difference films) that contribute greatly to thickness is being promoted. As a representative example of a thin phase difference film, a film (hereinafter referred to as a liquid crystal film) that orients a liquid crystal compound and fixes its orientation state can be cited. Liquid crystal compounds have a particularly large birefringence (Δn) compared to resins, so liquid crystal films can be particularly reduced in thickness compared to stretched films of resin films for obtaining the desired in-plane phase difference. Liquid crystal films are typically formed by applying a composition containing a liquid crystal compound to an oriented substrate and curing or hardening the coated film.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-222282 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The formed liquid crystal film is attached to a polarizing plate, and then the oriented substrate is peeled off. However, when the oriented substrate is peeled off from the liquid crystal film, peeling failure sometimes occurs. The present invention is completed to solve the above-mentioned problems, and its main purpose is to provide a method for producing an optical laminate with excellent appearance.

[0008] Means for solving problems

[0009] 1. A method for manufacturing an optical laminate according to an embodiment of the present invention is a method for manufacturing an optical laminate that sequentially comprises a polarizer containing a polarizer, an adhesive layer and a phase difference layer, the method comprising: a step of stacking a laminate of the polarizer, the phase difference layer and a supporting substrate with the aid of the adhesive layer to produce an intermediate laminate; and a step of bringing a peeling auxiliary component into contact with a surface on the polarizer side of the intermediate laminate to peel the optical laminate from the supporting substrate.

[0010] 2. In the method for producing an optical layered body described in 1 above, the peeling auxiliary member may be a peeling roller or a peeling bar.

[0011] 3. In the method for manufacturing the optical laminate according to 1 or 2 above, the retardation layer may be an orientation cured layer of a liquid crystal compound.

[0012] 4. In the method for manufacturing the optical laminate according to any one of 1 to 3 above, the adhesive layer may be an adhesive (Japanese:接着剤) layer.

[0013] 5. In the method for manufacturing the optical laminate according to any one of 1 to 4 above, a surface protection film may be further laminated, and the surface protection film is temporarily adhered to the surface on the support substrate side of the intermediate laminate in a peelable manner.

[0014] 6. In the method for manufacturing the optical laminate according to any one of 1 to 5 above, the nanoindentation elastic modulus of the adhesive layer measured at 25 °C may be 150 MPa or more.

[0015] 7. In the method for manufacturing the optical laminate according to any one of 1 to 6 above, the nanoindentation hardness of the adhesive layer measured at 25 °C may be 25 MPa or more.

[0016] 8. In the method for manufacturing the optical laminate according to any one of 1 to 7 above, the elastic recovery rate of the adhesive layer at 25 °C measured by nanoindentation may be 75% or less.

[0017] 9. In the method for manufacturing the optical laminate according to any one of 2 to 8 above, the diameter of the peeling roller may be 10 mm to 30 mm.

[0018] 10. Another aspect of the present invention provides an intermediate laminate. The intermediate laminate is an intermediate laminate sequentially including a polarizing plate containing a polarizer, an adhesive layer, a retardation layer, and a support substrate, and the peeling force P1 based on a 180° peeling test when peeling the laminate including the polarizing plate, the adhesive layer, and the retardation layer from the support substrate and the peeling force P2 based on a 180° peeling test when peeling the support substrate from the laminate including the polarizing plate, the adhesive layer, and the retardation layer satisfy the relationship of P1 < P2.

[0019] Advantages of the Invention

[0020] According to the present invention, a method for manufacturing an optical laminate that suppresses appearance defects such as wrinkles and breakage and obtains an optical laminate with extremely excellent appearance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a partial schematic cross-sectional view of an intermediate laminate according to an embodiment of the present invention.

[0022] Figure 2This is a schematic diagram showing an example of a peeling step according to an embodiment of the present invention.

[0023] Figure 3 This is a schematic diagram showing another example of the peeling step according to the embodiment of the present invention.

[0024] Description of Reference Numerals

[0025] 10 Polarizer

[0026] 11 Polarizer

[0027] 12. Protective layer

[0028] 20 Adhesive layer

[0029] 30 Phase difference layer

[0030] 40 Optical laminate

[0031] 50 Supporting substrate

[0032] 60 Surface protection film

[0033] 70 Stripping auxiliary member

[0034] 100 Intermediate laminate DETAILED DESCRIPTION

[0035] Hereinafter, preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0036] The method for producing an optical laminate according to an embodiment of the present invention is a method for producing an optical laminate comprising a polarizer, an adhesive layer and a phase difference layer in sequence, and comprises: a step of laminating a laminate of a polarizer, a phase difference layer and a supporting substrate via an adhesive layer to produce an intermediate laminate; and a step of bringing a peeling auxiliary member into contact with a surface of the intermediate laminate on the polarizer side to peel the optical laminate from the supporting substrate. Each step is described below.

[0037] A. Process for producing intermediate laminate

[0038] Figure 1It is a partial schematic cross-sectional view of an intermediate laminate according to an embodiment of the present invention. The intermediate laminate 100 includes an optical laminate 40 and a support substrate 50. The optical laminate 40 is sequentially laminated with a polarizing plate 10 containing a polarizer 11, an adhesive layer 20, and a retardation layer 30. The polarizing plate 10 typically includes a polarizer 11 and a protective layer 12 laminated on one surface of the polarizer. When other layers (such as the retardation layer) included in the optical laminate also function as a protective layer, the protective layer on the surface of the polarizer 11 where the protective layer 12 is not laminated can be omitted. Although omitted in the illustrated example, a protective layer can also be laminated on the surface of the polarizer 11 that does not have the protective layer 12. The adhesive layer 20 can be formed of any suitable adhesive or bonding agent. The retardation layer 30 can be a single layer or a laminate of two or more layers. The retardation layer can be an alignment cured layer of a liquid crystal compound (hereinafter also referred to as a liquid crystal alignment cured layer), or any suitable resin film. If the retardation layer is a liquid crystal alignment cured layer, an optical laminate with a thinner thickness can be provided. The intermediate laminate 100 in the illustrated example further includes a surface protection film 60 temporarily bonded to the surface of the support substrate 50 in a peelable manner. If the surface protection film 60 is further laminated, the peeling of the support substrate 50 can be performed more stably. The intermediate laminate 100 is preferably in a long strip shape. If the intermediate laminate 100 is in a long strip shape, an optical laminate can be obtained efficiently. In addition, the obtained optical laminate is also in a long strip shape and can be wound into a roll shape. In this specification, "long strip shape" means an elongated shape in which the length is sufficiently long relative to the width, for example, including an elongated shape in which the length is 10 times or more, preferably 20 times or more, relative to the width.

[0039] For the intermediate laminate, it is preferable that the peeling force P1 based on the 180° peeling test when peeling the laminate (i.e., the optical laminate) including the polarizing plate, the adhesive layer, and the retardation layer from the support substrate and the peeling force P2 based on the 180° peeling test when peeling the support substrate from the laminate including the polarizing plate, the adhesive layer, and the retardation layer satisfy the relationship P1 < P2. If P1 and P2 satisfy such a relationship, appearance defects such as wrinkles and breakage can be suppressed, and an optical laminate with extremely excellent appearance can be obtained. In this specification, P1 refers to the peeling force (N / 25 mm) measured by the 180° peeling test when peeling the optical laminate (i.e., the polarizing plate, the adhesive layer, and the retardation layer) from the intermediate laminate at a peeling speed of 500 mm / minute at 25°C with a glass plate laminated on the support substrate side of the intermediate laminate with a bandwidth of 25 mm and a tape length of 80 mm through an acrylic adhesive layer (thickness 23 μm). In addition, P2 refers to the peeling force (N / 25 mm) measured by the 180° peeling test when peeling the support substrate from the intermediate laminate at a peeling speed of 500 mm / minute at 25°C with a glass plate laminated on the polarizing plate side of the intermediate laminate with a bandwidth of 25 mm and a tape length of 80 mm through an acrylic adhesive layer (thickness 23 μm).

[0040] For the intermediate laminate, the total thickness T1 of the laminate (i.e., optical laminate) including the polarizer, the adhesive layer and the phase difference layer and the total thickness T2 of the supporting substrate and any surface protection film temporarily bonded in a removable manner preferably satisfy the relationship T1>T2. If T1 and T2 satisfy such a relationship, poor appearance such as wrinkles and breakage can be suppressed, and an optical laminate with extremely excellent appearance can be obtained.

[0041] A-1. Polarizer

[0042] The polarizing plate 10 includes a polarizer 11 and a protective layer 12 laminated on at least one side of the polarizer. If necessary, the polarizing plate 10 may include a protective layer on the side of the polarizer 11 where the retardation layer 30 is disposed.

[0043] A-1-1. Polarizer

[0044] The polarizer 11 is typically a resin film containing a dichroic substance (eg, iodine). Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films.

[0045] The thickness of the polarizer is, for example, 18 μm or less, preferably 15 μm or less, more preferably 12 μm or less, and further preferably 8 μm or less. The thickness of the polarizer is preferably 1 μm or more.

[0046] The polarizer preferably exhibits absorption dichroism at any wavelength in the range of 380 nm to 780 nm. The single-unit transmittance of the polarizer is, for example, 40.0% to 46.0%, preferably 41.0% to 45.0%, and more preferably 41.5% to 44.5%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more.

[0047] The polarizer can be produced by any appropriate method. Specifically, the polarizer can be produced using a single-layer resin film or a laminate including a substrate.

[0048] The method for making a polarizer from the above-mentioned monolayer resin film typically includes dyeing and stretching the resin film using dichroic substances such as iodine and dichroic dyes. As the resin film, for example, hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified films of ethylene-vinyl acetate copolymers can be used. The method can further include insolubilization treatment, swelling treatment, crosslinking treatment, etc. Such a manufacturing method is well known and commonly used in the art, so a detailed description is omitted.

[0049] The polarizer obtained using the laminate containing the above-mentioned substrate can be made, for example, using a laminate of a resin substrate and a resin film or a resin layer (representatively a PVA-based resin layer). Specifically, it can be made in the following manner: a PVA-based resin solution is applied to a resin substrate, dried to form a PVA-based resin layer on the resin substrate, and a laminate of the resin substrate and the PVA-based resin layer is obtained; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In the present embodiment, it is preferred to form a PVA-based resin layer containing a halide and a PVA-based resin on one side of the resin substrate. Stretching typically includes immersing the laminate in an aqueous boric acid solution for stretching. Furthermore, the stretching may further include stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in an aqueous boric acid solution as required. In addition, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment by being transported in the length direction while being heated so as to shrink the laminate by more than 2% in the width direction. Representatively, the manufacturing method of this embodiment includes sequentially implementing an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment and a drying shrinkage treatment on the laminate. By introducing auxiliary stretching, even when PVA is coated on a thermoplastic resin, the crystallinity of PVA can be improved, and high optical properties can be achieved. In addition, by improving the orientation of PVA in advance, when immersed in water in the subsequent dyeing process and stretching process, the problems of reduction and dissolution of the orientation of PVA can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the PVA molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by utilizing a drying shrinkage treatment to shrink the laminate in the width direction, high optical properties can be achieved. A protective layer is laminated on the peeling surface of the resin substrate peeled off from the obtained resin substrate / polarizer laminate, or on the surface opposite to the peeling surface, to obtain a polarizer. The details of the method for producing such a polarizer are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580 and Japanese Patent No. 6470455. The entire contents of these publications are incorporated herein by reference.

[0050] A-1-2. Protective layer

[0051] The protective layer 12 can be formed of any appropriate resin film that can be used as a protective layer of a polarizer. Specific examples of the resin that is the main component of the resin film include cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, cycloolefin resins such as polynorbornene, polyolefin resins, (meth) acrylic resins, acetate resins, etc.

[0052] In the manufacturing method of the embodiment of the present invention, the optical laminate 40 used is typically disposed on the visual recognition side of the image display device, and the protective layer 12 is disposed on the visual recognition side. Therefore, surface treatments such as hard coat (HC) treatment, antireflection treatment, antiadhesion treatment, antiglare treatment, etc. can be performed on the protective layer 12 as needed.

[0053] The thickness of the protective layer is, for example, 5 μm to 80 μm, preferably 10 μm to 50 μm, and more preferably 15 μm to 35 μm. It should be noted that in the case where the above surface treatment is performed, the thickness of the protective layer is the thickness including the thickness of the surface treatment layer.

[0054] A-2. Phase difference layer

[0055] The phase difference layer 30 typically has a circular polarization function or an elliptical polarization function. The phase difference layer can be a stretched film of a polymer thin film (phase difference film) or an orientation cured layer of a liquid crystal compound (liquid crystal orientation cured layer). In addition, the phase difference layer can be a single layer or can have a laminated structure (substantially a two-layer structure). Preferably, the phase difference layer is a liquid crystal orientation cured layer. If the phase difference layer is a liquid crystal orientation cured layer, it can contribute to the thinning of the optical laminate.

[0056] In one embodiment, the phase difference layer sequentially includes a first liquid crystal orientation cured layer and a second liquid crystal orientation cured layer from the polarizer side. In this embodiment, the phase difference layer as a whole (as a laminate of the first liquid crystal orientation cured layer and the second liquid crystal orientation cured layer) has a circular polarization function or an elliptical polarization function, and has the relationship of Re(450) < Re(550) < Re(650). Hereinafter, this embodiment will be described in detail. It should be noted that hereinafter, regarding the description of the phase difference layer in this item, when it is simply referred to as the "phase difference layer", it means the description of the phase difference layer as a whole, and when it is simply referred to as the "liquid crystal orientation cured layer", it means the description of the first liquid crystal orientation cured layer and the second liquid crystal orientation cured layer together.

[0057] The Re(550) of the phase difference layer is preferably 100 nm to 200 nm, more preferably 110 nm to 180 nm, further preferably 120 nm to 170 nm, and particularly preferably 130 nm to 150 nm. When the Re(550) of the phase difference layer is in such a range, the phase difference layer can be combined with a polarizer to exhibit a good circular polarization function or an elliptical polarization function.

[0058] The retardation layer preferably has a relationship of Re(450) < Re(550) < Re(650). That is, the retardation layer preferably exhibits an inverse-dispersion wavelength dependence in which the retardation value increases according to the wavelength of the measurement light. With such a structure, a good antireflection function can be achieved in a very wide wavelength band. Re(450) / Re(550) is, for example, more than 0.5 and less than 1.0, preferably 0.7 to 0.95, more preferably 0.75 to 0.92, and further preferably 0.8 to 0.9. Re(650) / Re(550) is preferably 1.0 or more and less than 1.15, more preferably 1.03 to 1.1.

[0059] In one embodiment, the Nz coefficient of the retardation layer can be, for example, 0.30 to 0.70. Therefore, the retardation layer exhibits a refractive index characteristic of nx > nz > ny. With such a configuration, reflection in the tilt direction can be well prevented, and a wide viewing angle of the antireflection function can be achieved. The Nz coefficient is preferably 0.35 to 0.65, more preferably 0.40 to 0.60, and further preferably 0.45 to 0.55.

[0060] Examples of the liquid crystal compound used in the liquid crystal alignment cured layer include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable (i.e., a liquid crystal monomer). If the liquid crystal compound can be polymerized, the alignment state of the liquid crystal compound can be fixed by polymerizing the liquid crystal compound after alignment. Here, the polymer formed by polymerization is non-liquid crystalline. Therefore, the formed liquid crystal alignment cured layer does not undergo a transition to a liquid crystal phase, a glass phase, or a crystal phase due to, for example, temperature changes peculiar to liquid crystalline compounds. As a result, the liquid crystal alignment cured layer becomes a retardation layer with extremely excellent stability that is not affected by temperature changes.

[0061] In one embodiment, the liquid crystal orientation solidification layer can be formed using a composition comprising a polymerizable liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer). In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and having liquid crystal properties. The polymerizable group refers to a group participating in the polymerization reaction, preferably a photopolymerizable group. Here, the photopolymerizable group refers to a group that can participate in the polymerization reaction by an active free radical, acid, etc. generated by a photopolymerization initiator. As a liquid crystal monomer, for example, the polymerizable mesogen compounds described in Japanese Patent Table 2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171 and GB2280445, etc. can be used. Specific examples of such polymerizable mesogen compounds include LC242 manufactured by BASF, E7 manufactured by Merck, and LC-Sillicon-CC3767 manufactured by Wacker-Chem.

[0062] The liquid crystal compound may have a thermotropic or lyotropic mechanism for expressing its liquid crystal properties. In addition, the liquid crystal phase may be a nematic liquid crystal or a smectic liquid crystal. From the viewpoint of ease of manufacture, a nematic liquid crystal having a thermotropic liquid crystal property is preferred.

[0063] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0064] The birefringence Δn of the liquid crystal orientation solidified layer is preferably 0.06 or more, more preferably 0.08 or more, further preferably 0.09 or more, and particularly preferably 0.10 or more. Δn can be, for example, 0.13 or less, and can be, for example, 0.12 or less. If Δn is in such a range, the desired in-plane phase difference can be achieved with a very thin thickness. As a result, the liquid crystal orientation solidified layer and the optical laminate can be further thinned, which can ultimately contribute to the significant thinning of the image display device.

[0065] The liquid crystal orientation solidified layer can show a reverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measuring light, a positive wavelength dispersion characteristic in which the phase difference value decreases according to the wavelength of the measuring light, or a flat wavelength dispersion characteristic in which the phase difference value hardly changes according to the wavelength of the measuring light.

[0066] In the case where the phase difference layer has a stacked structure, the first liquid crystal orientation solidification layer can function as a λ / 2 plate, and the second liquid crystal orientation solidification layer can function as a λ / 4 plate. Specifically, the Re(550) of the first liquid crystal orientation solidification layer is preferably 150nm to 300nm, more preferably 200nm to 270nm, and further preferably 220nm to 260nm; the Re(550) of the second liquid crystal orientation solidification layer is preferably 100nm to 200nm, more preferably 110nm to 160nm, and further preferably 120nm to 140nm. The thickness of the first liquid crystal orientation solidification layer can be adjusted in a manner to obtain the desired in-plane phase difference of the λ / 2 plate. In one embodiment, the thickness of the first liquid crystal orientation solidification layer can be, for example, 2.0μm to 4.0μm. In another embodiment, the thickness of the first liquid crystal orientation solidification layer is preferably 1.7μm or less, more preferably 1.6μm or less, and further preferably 1.5μm or less. In this case, the thickness of the first liquid crystal orientation solidification layer can be, for example, 1.3μm or more. In this way, according to an embodiment of the present invention, the thickness of the first liquid crystal orientation solidification layer can be made thinner than before, and linear unevenness can be suppressed. The thickness of the second liquid crystal orientation solidification layer can be adjusted in a manner to obtain the desired in-plane phase difference of the λ / 4 plate. Specifically, its thickness can be, for example, 0.8μm to 2.5μm. The angle between the slow axis of the first liquid crystal orientation solidification layer and the transmission axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 14° to 16°; the angle between the slow axis of the second liquid crystal orientation solidification layer and the transmission axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably 74° to 76°. It should be noted that the configuration order of the first liquid crystal orientation solidification layer and the second liquid crystal orientation solidification layer can be opposite, and the angle between the slow axis of the first liquid crystal orientation solidification layer and the transmission axis of the polarizer and the angle between the slow axis of the second liquid crystal orientation solidification layer and the transmission axis of the polarizer can be opposite.

[0067] The refractive index of the liquid crystal alignment cured layer may vary depending on the composition forming the liquid crystal alignment cured layer (substantially the type of liquid crystal compound, the type, amount, combination, blending amount, etc. of additives). LC1 The refractive index n of the second liquid crystal alignment curing layer LC2 They may be the same or different from each other (the refractive index n of the first liquid crystal alignment solidification layer may be LC1 The larger the refractive index n of the second liquid crystal alignment curing layer, the LC2 The refractive index n of the first liquid crystal alignment solidification layer is greater. LC1 The refractive index n of the second liquid crystal alignment solidified layer is preferably 1.55 to 1.75, and more preferably 1.60 to 1.70. LC2The refractive index n of the first liquid crystal alignment solidified layer is preferably 1.45 to 1.65, and more preferably 1.50 to 1.60. LC1 The refractive index n of the second liquid crystal alignment curing layer LC2 The refractive index n of the first liquid crystal alignment solidification layer is LC1 The refractive index n of the second liquid crystal alignment curing layer LC2 The absolute value of the difference may be, for example, 0.00 to 0.20. The refractive index of the liquid crystal alignment cured layer is typically based on the constitution of the composition forming the liquid crystal alignment cured layer in order to obtain desired optical characteristics.

[0068] It is also possible to introduce a side chain type thermotropic liquid crystal polymer into the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer (essentially the liquid crystal composition forming them). By introducing a side chain type thermotropic liquid crystal polymer, the effect of vertically aligning the liquid crystal monomer (vertical alignment) can be produced. As a result, the nz of the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer can be increased, and as a result, the Nz coefficient of the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer can be within the above-mentioned desired range. Finally, the Nz coefficient of the phase difference layer can be set to the above-mentioned desired range without setting the positive C plate described later.

[0069] As the side chain type thermotropic liquid crystal polymer, a copolymer having a monomer unit containing a thermotropic liquid crystal segment side chain and a monomer unit containing a non-liquid crystal segment side chain is typically used. When the polymer has a thermotropic liquid crystal segment in the side chain, the side chain type liquid crystal polymer can be oriented when the liquid crystal composition is heated to a predetermined temperature. In addition, when the side chain type polymer has a non-liquid crystal segment in the side chain, the non-liquid crystal segment interacts with the photopolymerizable liquid crystal monomer, which can produce an effect of vertically aligning the photopolymerizable liquid crystal monomer.

[0070] As the side chain type thermotropic liquid crystal polymer, a copolymer having a liquid crystal monomer unit represented by the general formula (I) and a non-liquid crystal monomer unit represented by the general formula (II) is preferably used.

[0071]

[0072] In formula (I), R 1 is a hydrogen atom or a methyl group, R 2 is a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and X 1 is -CO2- or -OCO-. a is an integer of 1 to 6, and b and c are 1 or 2 each independently.

[0073] In formula (II), R 3 is a hydrogen atom or a methyl group, R 4It is an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms, or a group represented by the following general formula (III).

[0074]

[0075] In formula (III), R 5 is an alkyl group having 1 to 5 carbon atoms, and d is an integer of 1 to 6.

[0076] The ratio of the liquid crystal monomer unit to the non-liquid crystal monomer unit in the side chain liquid crystal monomer can be appropriately set according to the purpose. The ratio (molar ratio) of the non-liquid crystal monomer to the total of the liquid crystal monomer unit and the non-liquid crystal monomer unit is preferably 0.05 to 0.8, more preferably 0.1 to 0.6, and further preferably 0.15 to 0.5. If this is the structure, a liquid crystal orientation solidified layer showing the desired refractive index characteristics (Nz coefficient) can be obtained.

[0077] The ratio of the liquid crystal monomer to the side chain type liquid crystal polymer in the liquid crystal composition can be appropriately set according to the purpose. When the content of the side chain type liquid crystal polymer is large, there is a tendency for the Nz coefficient to decrease, and when the content of the liquid crystal monomer is large, there is a tendency for the Nz coefficient to decrease. The content of the liquid crystal monomer is preferably 1.2 times to 20 times relative to the content of the side chain type liquid crystal polymer, more preferably 1.3 times to 10 times, further preferably 1.4 times to 9 times, and particularly preferably 1.5 times to 8 times. If this is constituted, a liquid crystal orientation solidified layer showing the desired refractive index characteristics (Nz coefficient) can be obtained.

[0078] Details of the side chain type liquid crystal polymer and the method for forming a liquid crystal alignment solidified layer having an Nz coefficient of less than 1.0 are described in Japanese Patent No. 6769921. The description of this patent is incorporated herein by reference.

[0079] The phase difference layer may further include a positive C plate. The refractive index characteristics of the positive C plate show the relationship of nz>nx=ny. The phase difference Rth(550) in the thickness direction of the positive C plate is preferably -20nm to -300nm, more preferably -30nm to -250nm, further preferably -40nm to -200nm, and particularly preferably -50nm to -150nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the positive C plate can be less than 10nm.

[0080] The positive C plate can be formed, for example, using a composition containing the above-mentioned side chain type liquid crystal polymer. As a specific example of the method for forming the positive C plate, there can be cited the method described in

[0020] to

[0028] of Japanese Patent Publication No. 2002-333642. At this time, the thickness of the positive C plate is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and further preferably 0.5 μm to 5 μm.

[0081] A-3. Supporting substrate

[0082] As the supporting substrate 50, any appropriate substrate can be used. Resin film is typically used. By laminating the phase difference layer on the supporting substrate, the operability of the phase difference layer can be improved. In the case where the phase difference layer is a liquid crystal orientation solidification layer, due to the thin thickness, the phase difference film may be damaged during film transportation in the manufacturing process. If a phase difference layer is laminated on the supporting substrate, the damage of the phase difference layer during transportation can be suppressed. In one embodiment, the supporting substrate can be an oriented substrate of a liquid crystal orientation solidification layer, i.e., a phase difference layer. That is, a liquid crystal composition forming a liquid crystal orientation solidification layer is applied to a supporting substrate, and the liquid crystal compound in the composition is oriented by the orientation restriction force of the supporting substrate, so that the liquid crystal compound is cured or hardened in an oriented state, thereby forming a liquid crystal orientation solidification layer. By laminating the supporting substrate 50 with the stack of the liquid crystal orientation solidification layer, i.e., the phase difference layer 30, and the polarizer 10 by means of an adhesive layer 20, an intermediate laminate 100 can be obtained. The supporting substrate 50 can be peeled off and removed in a subsequent process. That is, the supporting substrate 50 is laminated on the phase difference layer 30 in a peelable manner. In addition, when the phase difference layer has a laminated structure, it is preferable to use the same substrate as the substrate 50 as the alignment substrate of the first liquid crystal alignment solid layer and the second liquid crystal alignment solid layer.

[0083] The tensile elastic modulus of the supporting substrate 50 is preferably 3000 N / mm 2 If such a structure is adopted, poor peeling when peeling the supporting substrate can be suppressed. Specifically, it is possible to prevent or effectively suppress the phase difference layer from peeling off together with the substrate. The tensile elastic modulus of the supporting substrate is preferably 4000 N / mm 2 More preferably 5000N / mm 2 More than, more preferably 6000N / mm 2 Above, particularly preferably 6500N / mm 2 On the other hand, the tensile elastic modulus of the substrate can be, for example, 9000 N / mm 2 Below, in addition, for example, it can be 8500N / mm 2 The tensile modulus can be determined in accordance with JIS K7161.

[0084] The peeling force of the supporting substrate is preferably 1.2N / 50mm or less, more preferably 1.0N / 50mm or less, further preferably 0.8N / 50mm or less, and particularly preferably 0.7N / 50mm or less. On the other hand, the peeling force of the supporting substrate may be, for example, 0.01N / 50mm or more, and may be, for example, 0.02N / 50mm or more. If such a configuration is used, poor peeling when peeling the supporting substrate can be suppressed. Specifically, it is possible to prevent or well suppress the phase difference layer and the supporting substrate from peeling together.

[0085] As described above, the supporting substrate can be an orientation substrate of a liquid crystal orientation solidification layer, i.e., a phase difference layer. Therefore, the supporting substrate can have an orientation restriction force. The orientation restriction force can be imparted representatively by rubbing orientation, stretching substrate orientation, or light orientation. Preferably, the stretching substrate orientation or light orientation is used.

[0086] The supporting substrate can adopt any appropriate structure. Specifically, the supporting substrate can be a single film, or it can have a laminated structure of more than 2 layers (can be a laminate). As mentioned above, the supporting substrate is typically composed of a resin film. Therefore, the supporting substrate can be a single film of a resin film, or it can be a laminate comprising a first resin film and a second resin film. The cost and versatility of a single film are excellent. For a laminate, when a single film cannot take into account the desired orientation restriction force and the desired tensile elastic modulus, these characteristics can be supplemented with multiple resin films to take into account. The laminate can be a laminate of 3 layers further comprising a third resin film, or it can be a laminate of 4 layers further comprising a fourth resin film, or it can be a laminate of more than 5 layers. Each resin film contained in the laminate is typically laminated with the aid of an adhesive layer.

[0087] As materials constituting the resin film, representative examples include cellulose resins such as TAC, cycloolefin resins such as polynorbornene, (meth) acrylic resins, polyester resins such as PET and PEN, polyolefin resins such as polyethylene and polypropylene, and polycarbonate resins. As specific compositions of the substrate, preferably, a single film of a TAC film having an orientation-limiting force, and a laminate having a composition of a TAC film having an orientation-limiting force / adhesive layer / PET film can be cited.

[0088] The thickness of the substrate may vary depending on the material of the substrate, the structure of the substrate, etc. The thickness of the substrate may be, for example, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, or 40 μm or more. On the other hand, the thickness of the substrate may be, for example, 120 μm or less, 110 μm or less, or 100 μm or less.

[0089] A-4. Adhesive layer

[0090] The adhesive layer 20 is formed by any appropriate adhesive or adhesive. As adhesives, specific examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, quantity, combination and blending ratio of the monomers forming the base resin of the adhesive, as well as the blending amount, reaction temperature, reaction time, etc. of the cross-linking agent, an adhesive having desired properties corresponding to the purpose can be prepared. The base resin of the adhesive can be used only one type, or two or more types can be used in combination. In the case where the adhesive layer is an adhesive layer, the thickness of the adhesive layer is preferably 1μm to 30μm, more preferably 2μm to 20μm, and further preferably 3μm to 15μm.

[0091] As an adhesive, representative examples include active energy ray-cured adhesives. By using active energy ray-cured adhesives as adhesives, it is possible to achieve thinning of the adhesive layer, and as a result, an optical laminate with excellent bending properties can be obtained. Furthermore, it is possible to achieve high refractive index of the adhesive layer, and it is possible to reduce the refractive index difference with the adjacent liquid crystal orientation solidified layer. As a result, the reflection of the interface between the first adhesive layer and the first liquid crystal orientation solidified layer can be suppressed, so an optical laminate with excellent anti-reflection performance can be obtained. As an active energy ray-cured adhesive, free radical curing type, cation curing type, anion curing type, etc. can be selected as needed, for example, a mixture of free radical curing type and cation curing type can also be used in appropriate combination. As a free radical curing adhesive, for example, a compound (such as a monomer and / or oligomer) containing free radical polymerizable groups such as (meth) acrylate groups and (meth) acrylamide groups can be cited as an adhesive of a curing component. As an active energy ray-curable adhesive, by adjusting the type, combination and mixing ratio of double-bond-containing monomers and / or oligomers, cross-linking agents, etc., an active energy ray-curable adhesive having desired properties (e.g., storage modulus after curing) can be obtained. As active energy rays, for example, ultraviolet rays, visible light, infrared rays, and electron beams can be listed. Preferably, ultraviolet-curable adhesives. This is because of excellent versatility and operability. It should be noted that active energy ray-curable adhesives are well known in the industry, so the detailed description of the composition is omitted.

[0092] When the adhesive layer is an adhesive layer, the thickness of the adhesive layer is preferably 0.1 μm to 3.0 μm, more preferably 0.5 μm to 2.0 μm, and further preferably 0.8 μm to 1.5 μm. Such a thickness can contribute to thinning of the optical laminate.

[0093] A-5. Surface protection film

[0094] As described above, the intermediate laminate can be further temporarily bonded with a surface protection film on the supporting substrate side in a removable manner. The surface protection film typically comprises a substrate layer and an adhesive layer. The surface protection film is temporarily bonded to the supporting substrate side of the intermediate laminate by the adhesive layer in a removable manner.

[0095] A-5-1. Base material layer

[0096] The substrate layer is, for example, a resin film. As constituent materials of the resin film, for example, polyester, polyolefin, polyamide, polyimide, polycarbonate, polyacrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, and polyvinyl fluoride can be cited. As polyester, for example, polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate can be cited. As polyolefin, for example, polyethylene, polypropylene, polybutene, polymethylpentene, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-vinyl acetate copolymer, ethylene-(methyl)acrylate copolymer, and ethylene-vinyl alcohol copolymer can be cited. As polyamide, for example, nylon 6, nylon 6,6, and partially aromatic polyamide can be cited. The substrate layer can be composed of one material or more than two materials. The substrate layer can have a single-layer structure or a multilayer structure. In addition, when the substrate layer is a resin film, the substrate layer can be a stretched film or an unstretched film.

[0097] The thickness of the substrate layer is, for example, 10 to 200 μm, preferably 15 to 150 μm, more preferably 20 to 100 μm, and further preferably 25 to 75 μm. When the thickness is within the above range, the strength of the surface protection film as a support can be ensured, and a surface protection film with appropriate flexibility can be obtained.

[0098] The tensile elastic modulus of the substrate layer is preferably 1.0×10 8 Pa~1.0×10 10 Pa, more preferably 1.0×10 9 Pa~1.0×10 10 When the tensile modulus of elasticity of the substrate layer is within the above range, the workability of peeling and removing the supporting substrate from the intermediate laminate can be improved. It should be noted that the tensile modulus of elasticity is measured in accordance with JIS K 7161.

[0099] The elastic modulus of the substrate layer can be, for example, 2.2 kN / mm 2 ~4.8kN / mm 2 When the elastic modulus of the substrate layer is within such a range, deformation during transportation and / or lamination can be suppressed. In addition, the workability of peeling and removing the supporting substrate from the intermediate laminate can be improved. It should be noted that the elastic modulus is measured in accordance with JIS K 6781.

[0100] A-5-2. Adhesive layer for surface protection film

[0101] The adhesive layer (adhesive layer for surface protection film) can be formed by any appropriate adhesive. As a specific example, acrylic adhesive, rubber adhesive, silicone adhesive, polyester adhesive, urethane adhesive, epoxy adhesive, and polyether adhesive can be cited. By adjusting the type, quantity, combination and blending ratio of the monomers of the base resin forming the adhesive, as well as the blending amount, reaction temperature, reaction time, etc. of the cross-linking agent, an adhesive with desired characteristics corresponding to the purpose can be prepared. Only one kind of the base resin of the adhesive can be used. Two or more kinds can also be used in combination. The base resin is preferably an acrylic resin (that is, the adhesive layer is preferably composed of an acrylic adhesive).

[0102] The thickness of the adhesive layer of the surface protection film is preferably 3 μm to 100 μm, more preferably 4 μm to 60 μm, further preferably 5 μm to 40 μm, and particularly preferably 10 μm to 25 μm.

[0103] A-6. Lamination of polarizing plate and phase difference layer

[0104] The laminate of the polarizer, the phase difference layer and the supporting substrate is laminated by means of an adhesive or an adhesive forming the above-mentioned adhesive layer. The adhesive layer can be formed by any appropriate method. For example, when the adhesive layer is an adhesive layer, as a preferred formation method, gravure coating and slit coating can be cited.

[0105] In one embodiment, the intermediate laminate is in the shape of an elongated strip. The elongated intermediate laminate can be obtained, for example, by laminating an elongated polarizer with an elongated phase difference layer and a laminate of a supporting substrate. If an elongated polarizer and an elongated phase difference layer and a laminate of a supporting substrate are used, roll to roll can be used for lamination, and productivity can be improved. Typically, the laminate of an elongated phase difference layer and a supporting substrate is laminated on an elongated polarizer in a manner that the length directions of each other are consistent.

[0106] B. Supporting substrate peeling step

[0107] Next, the supporting substrate 50 stacked on the phase difference layer 30 is peeled off from the intermediate laminate 100. If the supporting substrate is peeled off from the intermediate laminate, an optical laminate 40 can be obtained. In the manufacturing method of an embodiment of the present invention, a peeling auxiliary member is brought into contact with the surface of the polarizer side of the intermediate laminate, and the optical laminate is peeled off from the supporting substrate. Usually, in the manufacturing method of an optical laminate, tension is applied to the supporting substrate to peel it from the intermediate laminate. In the manufacturing method of an embodiment of the present invention, a peeling auxiliary member is brought into contact with the surface of the polarizer side of the intermediate laminate, and tension is applied to the optical laminate to peel it. According to the manufacturing method of an embodiment of the present invention, an optical laminate having an extremely excellent appearance and suppressing poor appearance such as wrinkles and breakage can be provided.

[0108] The optical laminate is peeled off from the intermediate laminate in the following manner: the angle α formed by the intermediate laminate surface just before peeling and the peeling direction of the optical laminate is smaller than the angle β formed by the intermediate laminate surface just before peeling and the peeling direction of the support substrate. According to such an embodiment, it is possible to suppress appearance defects such as wrinkles and damage, and to peel the support substrate from the optical laminate well. As a result, an optical laminate with extremely excellent appearance can be provided.

[0109] The difference between the angle β and the angle α is preferably 60° or more, more preferably 90° to 180°. The angle α is preferably 30° or less, more preferably 0° to 20°. The angle β is preferably 60° or more, more preferably 90° to 180°.

[0110] The tension required for the peeling (peeling tension) is preferably 300 N or less, more preferably 200 N or less, and even more preferably 100 N or less.

[0111] Figure 2 1 is a schematic diagram showing an example of a stripping process according to an embodiment of the present invention. The intermediate laminate 100 is transported in such a manner that the supporting substrate 50 contacts the transport roller, so that the stripping auxiliary member 70 contacts the surface of the intermediate laminate 100 on the polarizer side (the surface of the optical laminate 40 that does not contact the supporting substrate 50 in the illustrated example). In the illustrated example, the stripping auxiliary member 70 is a triangular prism-shaped stripping rod. In the illustrated example, while the intermediate laminate 100 is transported upward, the stripping rod contacts the surface of the intermediate laminate 100 on the polarizer side (the surface of the optical laminate 40 that does not contact the supporting substrate 50 in the illustrated example), and the optical laminate 40 is stretched downward, thereby stripping the optical laminate 40 from the intermediate laminate 100, and the supporting substrate 50 is transported upward.

[0112] Figure 3: This is a schematic diagram of another example of the peeling process of an embodiment of the present invention. In this illustrated example, a peeling roller is used as a peeling auxiliary member. In this illustrated example, while the intermediate laminate 100 is conveyed upward, the peeling roller is brought into contact with the surface on the polarizer side of the intermediate laminate 100 (in the illustrated example, the surface of the optical laminate 40 that is not in contact with the supporting substrate 50), and the optical laminate 40 is stretched downward, thereby peeling the optical laminate 40 from the intermediate laminate 100, and conveying the supporting substrate 50 upward. When a peeling roller is used, the roller diameter is preferably 5 mm to 80 mm, more preferably 5 mm to 50 mm, and further preferably 10 mm to 30 mm. If the roller diameter is too large, the peeling strength becomes large, and sometimes good peeling cannot be performed. If the roller diameter is too small, sometimes the strength of the roller becomes insufficient and the peeling stability becomes insufficient.

[0113] The nanoindentation elastic modulus of the adhesive layer measured at 25°C is preferably 150MPa or more, more preferably 300MPa or more, further preferably 500MPa or more, and particularly preferably 600MPa or more. When the nanoindentation elastic modulus is within the above range, the supporting substrate can be well peeled off from the intermediate laminate. The nanoindentation elastic modulus is, for example, 1200MPa or less. In this specification, the nanoindentation elastic modulus of the adhesive layer refers to the value measured by the following method. The optical laminate is cut into 1 cm squares and fixed to the support as a measurement sample. The sample is placed on the table of a nanoindenter (e.g., manufactured by Hysitron, trade name "Triboindenter"), and a single indentation measurement is performed using a Berkovich (triangular pyramid) type indenter at a measurement temperature of 25°C. Specifically, the indenter is pressed into the maximum indentation depth of 1000nm from the phase difference layer side of the optical laminate including a polarizer and a phase difference layer toward the bonding layer at an indentation speed of 200nm / second, and pulled out at a pulling speed of 200nm / second. According to the load acting on the indenter-sample and the relative displacement of the indenter relative to the sample measured in the process of pressing the indenter into the sample (load application process) and the process of pulling out the indenter from the sample (unloading process), the nanoindentation elastic modulus (load-displacement determination) is calculated. Specifically, the load (maximum load Pmax) when pressed deepest and the area (contact projection area A) where the indenter contacts the sample are calculated by the following formula.

[0114] Nanoindentation hardness (MPa) = Pmax / A

[0115] The nanoindentation hardness of the adhesive layer measured at 25°C is preferably 25 MPa or more, more preferably 30 MPa or more, further preferably 40 MPa or more, and particularly preferably 50 MPa or more. When the nanoindentation hardness is in the above range, the supporting substrate can be well peeled off from the intermediate laminate. The nanoindentation hardness is, for example, 100 MPa or less. In this specification, the nanoindentation hardness of the adhesive layer refers to the value calculated by the following formula using the value measured by the above method. It is calculated by substituting the slope of the tangent of the unloading curve of the load-displacement curve obtained by the load-displacement measurement measured by the above nanoindentation measurement (contact rigidity S) and the above contact projection area A into the following formula.

[0116]

[0117] The nanoindentation elastic recovery rate of the adhesive layer measured at 25°C is preferably 75% or less, more preferably 70% or less, and further preferably 65% ​​or less. When the nanoindentation elastic recovery rate is within the above range, the supporting substrate can be well peeled off from the intermediate laminate. The nanoindentation elastic recovery rate is, for example, 40% or more. In this specification, the nanoindentation elastic recovery rate of the adhesive layer refers to the value measured by the following method. It refers to the value calculated by the following formula from the displacement (maximum displacement, hmax) and plastic deformation (hf) at the deepest indentation obtained by the above-mentioned nanoindentation measurement.

[0118] Nanoindentation elastic recovery rate = (hmax-hf) / hmax

[0119] Example

[0120] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. In addition, the measuring methods of each characteristic are as follows.

[0121] 1. Thickness

[0122] The measurement was performed using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C").

[0123] 2. Nanoindentation Measurement

[0124] The optical laminate obtained in the embodiment, comparative example and reference example is cut into 1 cm square, and the cut is fixed to the support (slide glass manufactured by Matsunami Glass Industries, thickness 0.8mm-1.0mm) in a manner that the polarizer side of the optical laminate is in contact with the support, as a measurement sample. The sample is set on the stage of a nanoindenter (manufactured by Hysitron, trade name "Triboindenter"), and a single indentation measurement is performed using a Berkovich (triangular pyramid) type indenter at a measurement temperature of 25°C. Specifically, the indenter is pressed from the phase difference layer side of the optical laminate including the polarizer and the phase difference layer toward the adhesive layer at an indentation speed of 200nm / second to a maximum indentation depth of 1000nm, and pulled out at a pulling speed of 200nm / second. The nanoindentation hardness, nanoindentation elastic modulus, and nanoindentation elastic recovery rate were calculated using the load-displacement curve obtained by the load acting between the indenter and the sample and the relative displacement of the indenter relative to the sample measured during the process of pressing the indenter into the sample (load application process) and the process of pulling the indenter out of the sample (unloading process). The three samples were measured and the average value was used as the result of each sample.

[0125] Nanoindentation hardness (GPa) = (load at deepest indentation: Pmax) / (contact area between indenter and sample (contact projection area A))

[0126]

[0127] Nanoindentation elastic recovery rate = (displacement at the deepest indentation (maximum displacement hmax) - plastic deformation (hf)) / maximum displacement hmax

[0128] 3. Peel force

[0129] The intermediate laminate produced in Manufacturing Examples 1 and 2 was cut into a band width of 25 mm and a length of 80 mm as a sample. The supporting substrate side of the sample was laminated to a glass plate (manufactured by Matsunami Glass Industries, Ltd., with a thickness of 1.3 mm) via an acrylic adhesive layer (thickness 23 μm), and the optical laminate (i.e., polarizer, adhesive layer, and phase difference layer) was peeled off from the intermediate laminate at a peeling speed of 500 mm / min at 25°C, and a 180° peeling test was performed to measure the peeling force. In addition, the polarizer side of the sample was laminated to a glass plate via an acrylic adhesive layer (thickness 23 μm), and a 180° peeling test was performed in the same manner to measure the peeling force (N / 25mm).

[0130] [Manufacturing Example 1] Preparation of Intermediate Laminated Body 1

[0131] 1. Preparation of polarizer

[0132] 1-1. Preparation of polarizer

[0133] A polyvinyl alcohol film having an average degree of polymerization of 2400, a saponification degree of 99.9 mol % and a thickness of 45 μm was prepared. The polyvinyl alcohol film was immersed in a swelling bath (water bath) at 20° C. for 30 seconds between rollers having different peripheral speed ratios to swell, while being stretched to 2.2 times in the conveying direction (swelling process), and then, while being immersed in a dyeing bath (an aqueous solution having an iodine concentration of 0.1 wt % and a potassium iodide concentration of 0.9 wt %) at 30° C. for 30 seconds to dye, and while being stretched to 3.3 times in the conveying direction based on the original polyvinyl alcohol film (a polyvinyl alcohol film that was not stretched at all in the conveying direction) (dyeing process). Next, the dyed polyvinyl alcohol film was immersed in a crosslinking bath (an aqueous solution having a boric acid concentration of 3.0 wt % and a potassium iodide concentration of 3.0 wt %) at 40° C. for 28 seconds, and stretched to 3.6 times in the conveying direction based on the original polyvinyl alcohol film (crosslinking process). Furthermore, the obtained polyvinyl alcohol film was immersed in a stretching bath (aqueous solution with a boric acid concentration of 4.0 wt % and a potassium iodide concentration of 5.0 wt %) at 61° C. for 60 seconds, stretched to 6.0 times along the conveying direction based on the original polyvinyl alcohol film (stretching process), and then immersed in a cleaning bath (aqueous solution with a potassium iodide concentration of 2.0 wt %) at 20° C. for 10 seconds (cleaning process). The cleaned polyvinyl alcohol film was dried at 40° C. for 30 seconds to prepare a polarizer. The thickness of the polarizer was 18 μm.

[0134] 1-2. Preparation of polarizing film

[0135] As an adhesive, an aqueous solution containing an acetoacetyl group-containing polyvinyl alcohol resin (average degree of polymerization of 1200, saponification degree of 98.5 mol%, acetoacetylation degree of 5 mol%) and methylol melamine in a weight ratio of 3:1 was used. Using this adhesive, a 30 μm thick transparent protective film (manufactured by Nippon Shokubai Co., Ltd.) formed of (meth) acrylic resin (modified acrylic polymer having a lactone ring structure) was laminated as a protective layer on one side (display element side) of the polarizer obtained above by a roll laminator, and a 49 μm thick transparent protective film formed of HC on a triacetylcellulose film (manufactured by Fujifilm Co., Ltd., trade name "TJ40UL") was laminated as a protective layer on the other side (visual recognition side), and then heated and dried in an oven (temperature of 90°C, time of 10 minutes) to produce a polarizing plate having transparent protective films laminated on both sides of the polarizer. The obtained polarizer had a single body transmittance of 41.7% and a polarization degree of 99.9%.

[0136] 2. Fabrication of phase difference layer

[0137] A photopolymerizable liquid crystal compound showing a nematic liquid crystal phase ("Paliocolor LC242" manufactured by BASF, the following chemical formula) was dissolved in cyclopentanone to prepare a solution having a solid content concentration of 20% by weight. A leveling agent ("Megafac F-563" manufactured by DIC), a photopolymerization initiator ("Omnirad907" manufactured by IGM Resins), and a crosslinking agent ("A-DCP" manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) were added to the solution to prepare a coating solution for forming a liquid crystal orientation solidification layer. A TAC film (thickness: 80 μm, tensile elastic modulus: 3391 N / mm 2 The above-mentioned coating solution for forming a liquid crystal orientation solidification layer was applied to the support substrate by a spin coater and heated at 100°C for 3 minutes to align the liquid crystal compound. After cooling to room temperature, the substrate was irradiated with a cumulative light intensity of 600 mJ / cm in a nitrogen atmosphere. 2 The liquid crystal compound was photocured by ultraviolet light to fix the orientation state of the liquid crystal compound. In this way, a laminate of a supporting substrate / liquid crystal orientation cured layer (thickness: 2 μm, Re (550): 270 nm) was obtained.

[0138]

[0139] 3. Preparation of Adhesive

[0140] A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA) and 1 part by weight of 4-hydroxybutyl acrylate (HBA) was placed in a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with ethyl acetate relative to 100 parts by weight of the monomer mixture (solid content), and nitrogen was introduced while slowly stirring to replace the nitrogen atmosphere. The liquid temperature in the flask was maintained at around 55°C and a polymerization reaction was performed for 7 hours. Then, ethyl acetate was added to the obtained reaction solution to prepare a solution of a (meth)acrylic acid polymer with a weight average molecular weight of 2 million and a solid content concentration adjusted to 30%.

[0141] 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / toluene diisocyanate adduct, manufactured by Tosoh Corporation, trade name “CORONATE L”) and 0.1 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., trade name “KBM403”) were added to 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution to prepare an acrylic adhesive composition.

[0142] 4. Fabrication of optical laminates

[0143] The liquid crystal alignment solidified layer was bonded to the surface of the TAC film on the opposite side to the HC layer of the polarizing plate via the adhesive layer (thickness 12 μm) formed using the adhesive obtained above, thereby obtaining an intermediate laminate 1 .

[0144] [Manufacturing Example 2] Preparation of Intermediate Laminated Body 2

[0145] 1. Preparation of Adhesive Composition

[0146] Unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone (manufactured by Daicel, trade name “PLACCELFA1DDM”) 20 parts by weight, acryloylmorpholine (manufactured by Kojin, trade name “ACMO”) 20 parts by weight, diethylacrylamide (manufactured by KJ Chemicals, trade name “DEAA”) 3 parts by weight, lauryl acrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name “LIGHT ACRYLATE LA”) 6.7 parts by weight, isostearyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name “ISTA”) 27 parts by weight, 1,9-nonanediol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name “LIGHT ACRYLATE 1,9ND-A”) 10 parts by weight, acrylic oligomer (manufactured by Toagosei Co., Ltd., trade name “ARUFON UP-1190”), 13.3 parts by weight of a photopolymerization initiator (2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one) (manufactured by IGM Resins BV, trade name “Omnirad 907”), and 3 parts by weight of a photopolymerization accelerator (diethylthioxanthone) (manufactured by Nippon Kayaku Co., Ltd., trade name “KAYACURE DETX-S”) were stirred at 50° C. for 1 hour to prepare an adhesive composition.

[0147] An intermediate laminate 2 was obtained in the same manner as in Production Example 1 except that the above-mentioned adhesive was used instead of the binder to form an adhesive layer (thickness 1.2 μm).

[0148] [Example 1]

[0149] The intermediate laminate 1 is placed on a flat table in a manner such that the supporting substrate is on the lower side. A peeling roller (diameter 20 mm) as a peeling auxiliary member is brought into contact with the surface of the intermediate laminate on the polarizer side. The end of the optical laminate (HC layer / TAC film (protective layer) / polarizer / acrylic film (protective layer) / adhesive layer / phase difference layer) contained in the intermediate laminate is peeled upward along the peeling roller, and the optical laminate is peeled from the supporting substrate to obtain an optical laminate. The nanoindentation measurement results and appearance evaluation results of the obtained optical laminate are shown in Table 1.

[0150] [Example 2]

[0151] An optical layered body was obtained in the same manner as in Example 1 except that the intermediate layered body 2 was used. Table 1 shows the results of the nanoindentation measurement and the appearance evaluation of the obtained optical layered body.

[0152] (Comparative Example)

[0153] An optical layered body was obtained in the same manner as in Example 2 except that the intermediate layered body 2 was placed so that the hard coat layer side of the polarizing plate was on the lower side. Table 1 shows the results of nanoindentation measurement and appearance evaluation of the obtained optical layered body.

[0154] (Reference example)

[0155] An optical layered body was obtained in the same manner as in Example 1 except that the intermediate layered body 1 was placed so that the hard coat layer side of the polarizing plate was on the lower side. Table 1 shows the results of nanoindentation measurement and appearance evaluation of the obtained optical layered body.

[0156] [evaluate]

[0157] The appearance of the optical layered body obtained in each of Examples, Comparative Examples and Reference Examples was visually evaluated. The evaluation criteria of the appearance were as follows.

[0158] (Appearance Evaluation Criteria)

[0159] Good: The resin substrate can be continuously peeled off in the longitudinal direction, and no wrinkles or foreign matter (such as substrate residue) are observed in the obtained polarizing plate.

[0160] Defective: Difficult to peel off continuously, and the polarizer obtained has wrinkles and foreign matter

[0161] [Table 1]

[0162]

[0163] [Industrial Application Possibility]

[0164] The optical layered body obtained by the production method according to the embodiment of the present invention is suitable for use in image display devices such as liquid crystal display devices and organic electroluminescent display devices.

Claims

1. A method for manufacturing an optical laminate, the optical laminate sequentially comprising a polarizer containing a polarizer, an adhesive layer, and a retardation layer. The manufacturing method includes: A step of laminating a laminate of the polarizer, the retardation layer, and a support substrate through the adhesive layer to produce an intermediate laminate. And A step of bringing a peeling assist member into contact with the surface on the polarizer side of the intermediate laminate and peeling the optical laminate from the support substrate.

2. The manufacturing method according to claim 1, wherein: The peeling assist member is a peeling roller or a peeling bar.

3. The manufacturing method according to claim 1, wherein: The retardation layer is an orientation cured layer of a liquid crystal compound.

4. The manufacturing method according to claim 1, wherein: The adhesive layer is an adhesive layer.

5. The manufacturing method according to claim 1, further comprising a step of laminating a surface protection film, the surface protection film being temporarily adhered to the surface on the support substrate side of the intermediate laminate in a peelable manner.

6. The manufacturing method according to claim 1, wherein: The adhesive layer has a nanoindentation elastic modulus of 150 MPa or more measured at 25°C.

7. The manufacturing method according to claim 1, wherein: The adhesive layer has a nanoindentation hardness of 25 MPa or more measured at 25°C.

8. The manufacturing method according to claim 1, wherein: The elastic recovery rate of the adhesive layer measured by nanoindentation at 25°C is 75% or less.

9. The manufacturing method according to claim 2, wherein: The diameter of the peeling roller is 10 mm to 30 mm.

10. An intermediate laminate, which sequentially comprises a polarizer containing a polarizer, an adhesive layer, a retardation layer, and a support substrate. When peeling the laminate including the polarizer, the adhesive layer, and the retardation layer from the support substrate, the peeling force P1 based on a 180° peeling test and the peeling force P2 based on a 180° peeling test when peeling the support substrate from the laminate including the polarizer, the adhesive layer, and the retardation layer satisfy the relationship P1 < P2.

Citation Information

Patent Citations

  • Liq. crystalline (LC) material

    DE19504224A1

  • Novel polymerizable liquid crystalline compounds

    DE4408171A1

  • Liquid crystalline reticulated polysiloxanes

    EP0066137A1

  • Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer

    EP0261712A1

  • Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups

    EP0358208A2